Emerging Dematiaceous and Hyaline Fungi Causing Keratitis in a Tertiary Care Centre From North India. Issue 7 (July 2020) - Ghosh, Anup; Kaur, Harsimran; Gupta, Amit; Singh, Shreya; Rudramurthy, Shivaprakash Mandya; Gupta, Sunita; Chakrabarti, Arunaloke
Abstract : Purpose: To report rare dematiaceous and hyaline fungal pathogens causing fungal keratitis (FK) at our center and review the published literature in this field. Methods: In a retrospective review of FK cases from 2005 to 2011, a total of 14 rare pathogens causing isolated cases of FK of a total of 393 isolates were revived from our collection and reconfirmed by using molecular techniques. The in vitro antifungal susceptibility testing (AFST) was performed against a 6-antifungal drug panel by the CLSI microbroth-dilution method. We reviewed the literature on keratitis due to these rare fungi. Results: Two novel fungi, Alternaria tenuissima and Epicoccum nigrum, were reported in addition to 6 dematiaceous (black pigmented) fungi ( Acrophialophora fusispora, Chaetomium globosum, Cladophialophora carionii, Nigrospora sphaerica, Papulaspora equi, and Scytalidium lignicola ), 5 hyaline (colorless) fungi ( Aspergillus tamarii, Fusarium chlamydosporum, Fusarium incarnatum, Fusarium lichenicola, and Fusarium sacchari ), and one yeast ( Trichosporon asahii ). Amphotericin B had good in vitro activity (minimum inhibitory concentration [MIC] ⩽1 μg/mL) against most dematiaceous fungi, but not hyaline fungi (MIC ≥1 μg/mL). Natamycin showed variable MIC, itraconazole and voriconazole had good in vitro activity, except in Fusarium species. Alternaria tenuissima and A. fusispora had a very high MIC (≥16 μg/mL) against echinocandins. Literature search revealed 27 FK cases due to F. lichenicola (n = 6), P. equi (n = 5), F. sacchari (n = 4), A. fusispora (n = 3), S. lignicola (n = 2), and others (n = 7), and more than 50% of these were reported from India. Conclusions: Plant fungal pathogens with variable antifungal susceptibility are an emerging cause of human keratitis with predominance of dematiaceous fungi. Identification and antifungal susceptibility testing are important for epidemiology and to optimize therapy and improve the patient outcome. Abstract : Supplemental Digital Content is Available in the Text.